2020
DOI: 10.1017/s0022149x20000905
|View full text |Cite
|
Sign up to set email alerts
|

Changes in land use affect anuran helminths in the South Brazilian grasslands

Abstract: Degradation and habitat loss of natural grasslands in Southern Brazil has a negative impact on native organisms, potentially including the composition of anuran helminth communities. Here, we characterized the richness, abundance, taxonomic composition, prevalence and intensity of helminth infection in four anuran species. Host anurans were collected in 34 ponds (19 in native grasslands with livestock and 15 in agricultural cultivation) from the highland grasslands in the Brazilian states of Santa Catarina and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 102 publications
(234 reference statements)
0
5
0
Order By: Relevance
“…Common invasion pathways or biological interactions (such as mutual facilitation or competition) may cause parasite species associations in hosts (Dallas et al, 2019) that, so far, have been noted in very few amphibian helminth community studies (Hamann et al, 2006a(Hamann et al, , 2010(Hamann et al, , 2013a(Hamann et al, , 2014. Many studies have shown the effect of anthropogenic habitats, such as soybean agriculture (Koprivnikar & Redfern, 2012), pasture and rice agriculture (Hamann et al, 2006b(Hamann et al, , 2020Campião et al, 2017), crop vs. livestock land uses (Draghi et al, 2020;Portela et al, 2020), and urban and pesticide polluted areas (King et al, 2007), on their composition, species richness and abundances. Helminths may provide clues to freshwater trophic state and water quality (Zargar et al, 2011), but, in general, the effect of freshwater habitat qualities on helminth communities in vertebrate hosts remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Common invasion pathways or biological interactions (such as mutual facilitation or competition) may cause parasite species associations in hosts (Dallas et al, 2019) that, so far, have been noted in very few amphibian helminth community studies (Hamann et al, 2006a(Hamann et al, , 2010(Hamann et al, , 2013a(Hamann et al, , 2014. Many studies have shown the effect of anthropogenic habitats, such as soybean agriculture (Koprivnikar & Redfern, 2012), pasture and rice agriculture (Hamann et al, 2006b(Hamann et al, , 2020Campião et al, 2017), crop vs. livestock land uses (Draghi et al, 2020;Portela et al, 2020), and urban and pesticide polluted areas (King et al, 2007), on their composition, species richness and abundances. Helminths may provide clues to freshwater trophic state and water quality (Zargar et al, 2011), but, in general, the effect of freshwater habitat qualities on helminth communities in vertebrate hosts remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in parasitism parameters in anthropized environments may be related to the parasite life cycle, quality of available resources, and aggregation and condition of hosts (revision in Becker et al 2015). In the literature, an increase in rates of parasitism by helminths with an intensification of disturbance is frequently identified (Mckenzie & Townsend 2007; Portela et al 2020). However, when it is not considered that different species’ life cycles can be affected differently by anthropization, the effect on parasites can be masked.…”
Section: Resultsmentioning
confidence: 99%
“…Helminth parasites can infect their hosts through direct contact of the larvae or through intermediate hosts. Infection parameters (e.g., abundance, prevalence) can be affected by aspects such as diet (Silva et al 2019), microhabitat use (Brito et al 2014) and host density (Kelehear et al 2012), and these factors can be affected by environmental alterations, such as the agricultural land use (Portela et al 2020). Among the problems that agricultural land use can cause in helminths, for example, are the reduction in the immune response or competence of the hosts (Kiesecker 2002), changes in habitat (Sillero et al 2020) and changes in resource availability (Becker et al 2015) that may imply changes in parasitism patterns (Brito et al 2014; Becker et al 2015; Kiesecker 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that land-use changes can influence helminths, although the effects seem to depend on both host's and parasite's ecology (e.g. Chakraborty et al ., 2019 ; Portela et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%